Learning innovation using augmented reality for interactive learning experiences - Yudiernawati, Atti; Wahyuni, Tavip Dwi; Suryani, Pudji (Jurnal Konseling dan Pendidikan, 2025)
This study explores the potential of learning innovations using Augmented Reality (AR) to enhance the interactive learning experience in educational settings. AR, a technology that overlays digital information on the real world, provides immersive and engaging experiences that support diverse learning styles. This qualitative research employs a literature review methodology to analyze and synthesize findings from various studies on AR in education. The literature highlights the growing interest in AR as an educational tool, focusing on its ability to increase student engagement, improve knowledge retention, and foster active participation. AR enables learners to interact with 3D models, simulations, and other dynamic content, making abstract concepts more accessible and understandable. Additionally, AR promotes collaboration among students, allowing for shared learning experiences in both physical and virtual spaces. Despite its advantages, challenges such as technological accessibility, high implementation costs, and the need for teacher training remain barriers to widespread adoption. This paper discusses the implications of AR for educators and policymakers and suggests directions for future research to address these challenges. The findings underscore the transformative potential of AR in reshaping traditional learning environments, paving the way for more interactive and personalized learning experiences. By integrating AR, educators can create more engaging and effective learning experiences that cater to the needs of 21st-century learners.